Integrated in silico-in vitro characterization, identification and disruption of the intermolecular interaction between SH3 domain-containing protein kinases and human pituitary tumor-transforming gene 1 - Li, Yanan; Li, Mengmeng; Min, Weijie; Han, Guosheng; Wang, Laixing; Chen, Chao; Li, Zifu; Zhang, Yuhui; Li, Jianmin; Yue, Zhijian (General physiology and biophysics, 2017)
The human pituitary tumor-transforming gene-1 (hPTTG1) has been found to be overexpressed in various cancers. Accumulated evidences implicate that some of protein kinases can specifically recognize two PXXP motifs at hPTTG1 C-terminus through their Src homology (SH3) domain and then phosphorylate the protein by their catalytic domain. Here, we integrate in silico analysis and in vitro assay to characterize the intermolecular interaction between the two hPTTG1 motif peptides 161LGPPSPVK168 (M1P) and 168KMPSPPWE175 (M2P) and the SH3 domains of Ser/Thr-specific protein kinases MAP3K and PI3K. It is identified that the two peptides bind to MAP3K SH3 domain with a moderate affinity, but cannot form stable complexes with PI3K SH3 domain. Long time scale molecular dynamics (MD) simulations reveal that the M1P peptide can fold into a standard poly-proline II helix that is bound in the peptide-binding pocket of MAP3K SH3 domain, while the M2P peptide gradually moves out of the pocket during the simulations and finally forms a weak, transient encounter complex with the domain. All these suggest that the MAP3K M1P site is a potential interacting partner of MAP3K SH3 domain, which may mediate the intermolecular recognition between hPTTG1 and MAP3K.